The Application Of Preventive Replacement Strategy On Machine Component In Deteriorating Condition – A Case Study In The Processing Industries. - Ahmad, Rosmaini; Kamaruddin, Shahrul; Mokhtar, Mohzani; Almanar, Indra Putra (2006)
The operation of a particular component in deteriorating condition will lead to a high machine downtime. This is due to the failure of component at unexpected time. As a result it will increase cost of maintenance and production lost. One of the solutions to this matter is to use Preventive Replacement (PR).